2012
DOI: 10.1007/s11207-012-0182-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Helioseismic Power-Spectrum Diagram of a Sunspot

Abstract: The continuous high spatial-resolution Doppler observation of the Sun by Solar Dynamics Observatory / Helioseismic and Magnetic Imager allows us to compute helioseismic k-ω power-spectrum diagram using only oscillations inside a sunspot. Individual modal ridges can be clearly seen with reduced power in the k-ω diagram constructed by use of 40-hour observation of a stable and round sunspot. Comparing with the k-ω diagram obtained from a quiet-Sun region, inside the sunspot the f -mode ridge gets more power redu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
(24 reference statements)
3
6
0
Order By: Relevance
“…Even though the p-mode has a peak of power around the 5 minute period, its higher frequency tail may contain some power at the 3 minute period. Observational results have been reported that are consistent with this driving, which include the similarity of the frequency spectrum and oscillating pattern with the quiet Sun (Zhao & Chou 2013;Krishna Prasad et al 2015), the p-mode absorption coefficient (Braun 1995), the inward traveling wave power at the umbra-penumbra boundary (Penn & Labonte 1993), and the direct detection of peculiar velocity pattern (Beck 2010).…”
Section: Introductionsupporting
confidence: 64%
“…Even though the p-mode has a peak of power around the 5 minute period, its higher frequency tail may contain some power at the 3 minute period. Observational results have been reported that are consistent with this driving, which include the similarity of the frequency spectrum and oscillating pattern with the quiet Sun (Zhao & Chou 2013;Krishna Prasad et al 2015), the p-mode absorption coefficient (Braun 1995), the inward traveling wave power at the umbra-penumbra boundary (Penn & Labonte 1993), and the direct detection of peculiar velocity pattern (Beck 2010).…”
Section: Introductionsupporting
confidence: 64%
“…A high-resolution − diagram is a tool to resolve this issue. A successful attempt to construct such a diagram from sunspot data taken by SDO/HMI, reported recently by Zhao and Chou (2013), convincingly shows that the positions of the ridges are quite similar to the quiet Sun, except for the displacement produced by a different phase speed of waves beneath sunspots. Therefore, the latest data not not seem to confirm the presence of a particular resonant cavity in the sunspot atmosphere.…”
Section: Resonance Cavity Model For Chromospheric Wavesmentioning
confidence: 89%
“…It is systematically found in observations that more wave power travels toward the umbra than leaves the umbra in horizontal direction (Section 5). One of the most conclusive examples of the − diagram in sunspots recently constructed by Zhao and Chou (2013) from SDO/HMI data shows a very similar system of ridges with reduced power at the location of -modes, and, especially of the -mode. The − diagram also shows that convention in sunspots is significantly suppressed and its spectrum is shifted to large spatial scales.…”
Section: Magneto-acoustic Wavesmentioning
confidence: 89%
See 1 more Smart Citation
“…Evidently, even with such high-resolution (0.1 ) observations we still cannot confirm the existence of 5-min oscillations in the chromospheric umbrae (see Figure 2 (d) − (g)). Zhao & Chou (2013) suggested that resonant oscillations exist inside the sunspot, primarily inside the sunspot penumbra. In adition to the overall power enhancement over the penumbra, there are tiny speckles of power scattered everywhere.…”
Section: High and Low Frequency Oscillations At Different Heightsmentioning
confidence: 99%